A Convergent Approach for the Synthesis of C14–C26 Fragment of Anticancer Drug Eribulin Mesylate - Nasam, Rajesh; Pabbaraja, Srihari (Synthesis, 2023)
The stereoselective synthesis of C14–C26 fragment of eribulin is reported in a convergent way by coupling of fragment C14–C19 with fragment C20–C26 that are accessible from commercially available raw materials crotonic acid and 1,4-butanediol. The key steps involved in this practical approach are Hosomi–Sakurai asymmetric alkylation, Maruoka allylation, Noyori reduction, silver-catalyzed one-pot rearrangement, and intramolecular cyclization.
Keywords: natural product; allylation; Noyori reduction; Wittig reaction; convergent approach